Review of the monograph# Mateusz Kuczabski's Health Security Implications for National Security - Ilona Urych (Open Journal of Pain Medicine - Peertechz Publications, 2022)
The reviewed monography by Mateusz entitled J. Kuczabski "Health Security Implications for National Security" fills a significant gap, because, despite the availability of extensive foreign and domestic literature on health safety, it is difficult to find a commonly agreed definition. The potentially useful distinction between "health and safety", "health system", "healthcare system" and "health security" has not been developed in the literature. Interestingly, the author notes significant discrepancies in the understanding and application of the concept of health security existing even in UN agencies, for example between the United Nations Development Program (UNDP) and the World Health Organization (WHO). The results of the research by M. J. Kuczabski presented and prepared by the author may serve as an indication of the direction of future transformations in the field of health security and health policy in relation to the Polish security system.